Classical Models, Sonata Theory, Equal Division of the Octave and Two Nineteenth-Century Symphonic Movements: Comparing Analytical Approaches - Howard Cinnamon (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
The first movements of Tchaikovsky’s Fourth and Brahms’s Third Symphonies are examined from the perspective of earlier models of sonata form (those of Kollmann, Galeazzi, and Czerny). The author demonstrates how they adhere to the models in remarkably consistent ways, and shows how analyses based on the models can prove valuable in the study of a group of pieces with similar unconventional harmonic structures. Aspects of Hepokoski and Darcy’s Sonata Theory are incorporated in each case to show how its conclusions differ from—and how they might complement—those arrived at through the application of earlier models.